Trade Costs, Conflicts, and Defense Spending - Michael Seitz; Alexander Tarasov; Roman Zakharenko (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
This paper develops a quantitative model of trade, military conflicts, and defense spending. Trade liberalization between two countries reduces probability of an armed conflict between them, causing both to cut defense spending. This in turn causes a domino effect on defense spending by other countries. As a result, both countries and the rest of the world are better off. We estimate the model using data on trade, conflicts, and military spending. We find that, after reduction of costs of trade between a pair of hostile countries, the welfare effect of worldwide defense spending cuts is comparable in magnitude to the direct welfare gains from trade.
urn:nbn:de:bvb:19-epub-15742-0
Keywords: C5; C6; F13; F51; H56; 330; general equilibrium; gains from trade; defense spending